Impact of Side Branch Lesion Length on Clinical Outcome after Coronary Stenting Techniques in Patients with Coronary Artery Bifurcation Disease: A Meta-Analysis. Issue 3 (30th September 2022) - Kan, Junyan; Luo, Shuai; Wang, Dongchen; Cai, Dandan; Zhang, Xiaojuan; Kan, Jing
Abstract : Objective: The optimal percutaneous coronary intervention (PCI) technique for bifurcation lesions remains controversial, especially considering the variability of the side branch (SB). A provisional stenting technique is currently recommended in most cases. This meta-analysis aimed to compare outcomes of different bifurcation PCI strategies, clarifying their scope of application. Methods: Randomized controlled trials comparing PCI strategies for coronary bifurcation lesions were systematically retrieved from PubMed, Cochrane, Web of Science, and EBSCO literature databases without limitations on published date or language. Major adverse cardiovascular events (MACEs) were stipulated as main outcomes. Secondary outcomes of interest were all-cause mortality, cardiovascular mortality, target lesion revascularization (TLR), target vessel revascularization, myocardial infarction (MI), and stent thrombosis. Both pooled analysis and sub-group analysis were performed. Results: Twenty-three randomized controlled trials with 6380 participants were included. Eighteen studies compared the provisional strategy with 2-stent approaches. No significant difference in MACEs (relative risk (RR), 1.16; 95% confidence interval (CI), 0.90–1.48; I 2 = 62%) was found between 1-stent and 2-stent techniques. However, when SB lesion length was used as the separation condition, the 2-stent strategy was associated with fewer MACEs (RR, 1.87; 95% CI, 1.46–2.41; I 2 = 70%), TLRs (RR, 2.13; 95% CI, 1.50–3.02; I 2 = 59%), and MIs (RR, 2.17; 95% CI, 1.19–3.95; I 2 = 52%) than the provisional strategy in those where SB lesions measured >10 mm long. Conclusions: In the current work, there was no significant difference between 1-stent and 2-stent techniques in terms of MACEs or secondary outcomes. However, 2-stent approaches have clinical advantages over the provisional strategy in bifurcation when the SB lesion length is >10 mm due to fewer cases of TLR and MI.